Similar Connotation in Chronic Hepatitis B and Nonalcoholic Fatty Liver Patients with Dampness-Heat Syndrome. (8th April 2013) - Dai, Jianye; Sun, Shujun; Cao, Jianmei; Zhao, Yu; Cao, Huijuan; Zheng, Ningning; Fang, Junwei; Wang, Yang; Zhang, Wei; Zhang, Yongyu; Hu, Yiyang; Cao, Zhiwei
Abstract : The phenomenon that the same syndrome turns up in different diseases appears in the sight of people around the world, which raises the thought for possibility of "Same Treatment for Different Diseases." Actually, treatment based on ZHENG classification in Traditional Chinese Medicine could bring revelation for the former finding. The dampness-heat syndrome in chronic hepatitis B and nonalcoholic fatty liver is regarded as the breakthrough point. We discussed the molecular mechanism of similar connotation that exists in chronic hepatitis B and nonalcoholic fatty liver by metabonomics to give the modern understanding of dampness-heat syndrome. Both urine and serum metabolic profiling revealed that obvious differences existed between dampness-heat syndrome and non-dampness-heat syndrome but the commonality was proved to appear in chronic hepatitis B and nonalcoholic fatty liver patients with dampness-heat syndrome. Furthermore, disorder of body fluid metabolism, decline in digestive capacity, and imbalance of intestinal flora were found to be the new guiding for treatment, with the hope to provide the basis for Chinese personalized medicine.